Responding To: In Defense of Merit in Science - Georgina Tuari Stewart (Journal of Global Indigeneity)
This commentary responds to a perspective article by a group of 27 co-authors, most affiliated to universities in the USA, with a sprinkling of international others: two each from France and Germany; one each from the UK, Australia and New Zealand; and three listing dual-country affiliations to USA as well as Israel, Germany and Australia. The perspective article claims that science is in serious danger from the replacement of merit by identity as the basis for assessments in science education, hiring of scientists, and research funding decisions. Although stopping just short of saying this ‘is’ happening, its purpose is to issue a warning that the future of science is under threat, if such trends were to continue. Given its relevance to science and science education in Aotearoa New Zealand, it is important for us as Māori and non-Māori to understand the claims and arguments it makes. Below, I list and discuss its key ideas, summarise its scholarly flaws, and comment on its meta-level significance in context.